Effectiveness Of Using A Combination Of Ginger And Honey Herbal Medicine To Reduce Productive Cough In Young Adults - Zuriani Rizki; Rezqiqah Aulia Rahmat; Halbina Famung Halmar (International Journal of Health Sciences, 2025)
A productive cough is a common respiratory complaint among young adults and can disrupt daily activities. Herbal remedies such as ginger and honey have long been trusted as an alternative therapy for cough relief due to their anti-inflammatory, antimicrobial, and expectorant effects. This study aimed to determine the effectiveness of a combination of ginger and honey in reducing productive cough in young adults. This study uses a quasi -experimental design with a one-way approach. group Pretest - posttest. The research sample consisted of 30 young adult respondents with productive cough, selected using purposive sampling technique. Cough severity was measured using a cough scale questionnaire before and after the intervention. Data analysis used the Wilcoxon test. Signed Rank Test. The results of the study showed a significant decrease in the level of productive cough after administering a combination of ginger and honey with a p value = 0.000 (<0.05). The conclusion of this study is that the combination of ginger and honey is effective in reducing productive cough in young adults.